2020
DOI: 10.1530/eje-19-0957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on insulin sensitivity, hyperinsulinemia and ectopic fat in black South African women: a randomized controlled trial

Abstract: Objective We investigated the effects of a 12-week exercise intervention on insulin sensitivity (SI) and hyperinsulinemia and associated changes in regional and ectopic fat. Research design and methods Healthy, black South African women with obesity (mean age 23 ± 3.5 years) and of isiXhosa ancestry were randomised into a 12-week aerobic and resistance exercise training group (n = 23) and a no exercise group (control, n = 22). Pre and post-intervention testing included assessment of SI, insulin response to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…This study is a secondary analysis from a randomised control trial, for which information on recruitment, retention, methods and sample size determination have previously been reported [28]. Primary and secondary endpoints (insulin sensitivity, peak oxygen consumption [VO 2peak ] and body composition) from the original randomised control trial have been previously reported [29] and additional measures of mitochondrial respiration, skeletal muscle lipidomics, metabolomics and protein content not determined in the original study were analysed by the authors of this paper. All participants were recruited from a low socioeconomic urban area in Cape Town between July 2015 and December 2016.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study is a secondary analysis from a randomised control trial, for which information on recruitment, retention, methods and sample size determination have previously been reported [28]. Primary and secondary endpoints (insulin sensitivity, peak oxygen consumption [VO 2peak ] and body composition) from the original randomised control trial have been previously reported [29] and additional measures of mitochondrial respiration, skeletal muscle lipidomics, metabolomics and protein content not determined in the original study were analysed by the authors of this paper. All participants were recruited from a low socioeconomic urban area in Cape Town between July 2015 and December 2016.…”
Section: Methodsmentioning
confidence: 99%
“…1. The exercise intervention consisted of 12 weeks of supervised aerobic and resistance training at a moderate-vigorous intensity for 40-60 min, 4 days/week by a trained facilitator, which included a 50% time split between the two modalities [29]. Aerobic exercises included dance, running, skipping and stepping at a moderate-vigorous intensity (75-80% peak heart rate [HR peak ]).…”
Section: Week Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional body fat distribution (gynoid and android fat as a proportion of total fat mass (%FM)) was characterized as previously described [30,31]. After a standardized meal (Energy: 2553 kJ), magnetic resonance imaging (MRI) was used to determine VAT and SAT volumes using a 3 Tesla whole-body human MRI scanner (MAGNETOM Skyra, Siemens Medical Solutions, Erlangen, Germany) as previously described [32].…”
Section: Body Composition and Body Fat Distributionmentioning
confidence: 99%
“…The participants involved in this cross-sectional study were young (23 (21-27) years), obese (33.9 ± 2.8) kg/m 2 ) women ( Table 1). The time course response of the glucose, insulin and c-peptide in response to the FSIGT have been recently published [32]. Self-reported dietary fat intake comprised of 34% of total energy (%E), of which 9.5%E was from SFA, 11.4%E from MUFA and 7.9%E from PUFA (Table 2).…”
Section: Participant Characteristics and Dietary Intakementioning
confidence: 99%